Family Burden in Caring for Family Members with Schizophrenia : A Systematic Review - Priyana Putra, Rausan Fikri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Introduction Schizophrenia cases are increasing worldwide, especially in low- and middle-income countries. Schizophrenia is a serious and chronic mental illness that requires care for family members, but in practice, this becomes a burden for the family, both objective and subjective.Objective This systematic review aims to identify the main focus regarding the burden on families as caregivers of family members with schizophrenia.Method The research method uses PRISMA with a systematic approach and selection process with literature sources searched from the Scopus, PubMed, ScienceDirect, and ProQuest databases and manual searches with the keywords "Caregiver Burden OR Family Burden AND Schizophrenia". The results of the articles that were filtered and obtained were then evaluated using the Joanna Briggs Institute (JBI) tool.Result Three main themes were found to be related to the family's burden as caregivers of a family member with schizophrenia. The three themes are caregiver burden, stigma, and health services.Conclution Findings suggest that family burden on caregivers influences the family's ability to care for patients with schizophrenia. The family's burden as caregivers is an important indicator for the provision of mental health services.